2011
DOI: 10.4103/2152-7806.83731
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity in transcranial motor-evoked potential monitoring during neurosurgical operations

Abstract: Background:Intraoperative transcranial motor-evoked potential (TCMEP) monitoring is widely performed during neurosurgical operations. Sensitivity and specificity in TCMEP during neurosurgical operations were examined according to the type of operation.Methods:TCMEP monitoring was performed during 283 neurosurgical operations for patients without preoperative motor palsy, including 121 spinal operations, 84 cerebral aneurysmal operations, and 31 brain tumor operations. Transcranial stimulation at 100–600 V was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…Our CMAP normalization was shown to be effective under the constant administration of anesthetics. Although CMAP normalization provided only a very minor improvement in the sensitivity and specificity of MEP monitoring, as previously reported [19], CMAP normalization is necessary when using MEP to predict functional recovery from compressive spinal and spinal nerve disease.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Our CMAP normalization was shown to be effective under the constant administration of anesthetics. Although CMAP normalization provided only a very minor improvement in the sensitivity and specificity of MEP monitoring, as previously reported [19], CMAP normalization is necessary when using MEP to predict functional recovery from compressive spinal and spinal nerve disease.…”
Section: Discussionmentioning
confidence: 73%
“…Langeloo et al also showed that an 80% reduction in amplitude was the threshold point in MEP with EMG recording in spinal surgery [3]. We previously reported that in 121 spinal operations for patients without preoperative motor palsy (MRC grading P 3/5), the sensitivity and specificity of MEP by EMG recording with CMAP normalization was 100% and 96.4%, respectively, using a criterion of an 80% reduction in amplitude [19,20]. These results are consistent with those of Langeloo et al [3].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is well known that MEPs are highly sensitive compared to SSEPs, but while they seem to be influenced by the same systemic factors, MEPs are more vulnerable to ischemic injuries, and thus experience more changes in amplitude than SSEPs due to the nature of their blood supply [12,21,25]. The anterior spinal artery (ASA) supplies around 75% of the spinal cord, which includes gray matter and anterior horn cells [26,27].…”
Section: Discussionmentioning
confidence: 99%